Effect of erythropoietin on hepcidin expression in hemojuvelin-mutant mice - Krijt, Jan; Jonásová, Anna; Neuwirtová, Radana; Necas, Emanuel (Blood cells, molecules & diseases, 2010)
Transcription of the hepcidin (Hamp) gene is controlled by iron stores and the rate of erythropoiesis. Functional hierarchy between these two stimuli has not yet been completely established. It is also not known whether the erythropoiesis-related downregulation of Hamp expression utilises the bone morphogenetic protein/hemojuvelin (Bmp/Hjv) pathway. Hemojuvelin-mutant (Hjv-/-) mice treated with erythropoietin (EPO) at 50IU/mouse/day for three days displayed marked decrease in Hamp mRNA, demonstrating that hemojuvelin is not an indispensable component in EPO-induced Hamp gene downregulation. Irradiation of Hjv-/- mice prevented the EPO-induced decrease of Hamp mRNA, highlighting the role of erythropoiesis in Hamp gene regulation by EPO. After a single injection of EPO, Hamp mRNA levels were not significantly changed at 6h, but decreased at 10 and 24h. Chronic bleeding decreased hepatic Bmp6 mRNA levels; however, repeated EPO treatment did not change Bmp6 mRNA, suggesting that the erythropoietic regulator(s) act independently of the Bmp/Hjv pathway. Pretreatment of C57BL/6 mice with iron (5mg/mouse) almost completely inhibited the EPO-induced decrease of Hamp mRNA. This result suggests that administration of EPO to patients with transfusional iron overload is probably not associated with the risk of additional absorption of substantial amounts of iron from the diet.
Keywords: kationické antimikrobiální peptidy; genetická transkripce; játra; Hemochromatosis Protein; Membrane Proteins; Iron Overload; erytropoéza; messenger RNA; erythropoetin; regulace genové exprese; Down-Regulation; Transcription, Genetic; Female; hepcidiny; Erythropoietin; Recombinant Proteins; zvířata; myši; GPI-Linked Proteins; Bone Morphogenetic Protein 6; myši inbrední C57BL; down regulace; Hepcidins; Antimicrobial Cationic Peptides; Mice; myši knockoutované; Erythropoiesis; rekombinantní proteiny; Ferric Compounds; RNA, Messenger; ženské pohlaví; Gene Expression Regulation; Liver; Male; Mice, Knockout; Mice, Inbred C57BL; protein hemochromatózy; železité sloučeniny; kostní morfogenetický protein 6; membránové proteiny; Animals; přetížení železem; GPI-vázané proteiny; Polysaccharides; polysacharidy; mužské pohlaví